THE AUDITOR’S COMMITMENT TO INTERNATIONAL AUDITING STANDARD NO. (570) AND ITS IMPACT ON ACHIEVING SUSTAINABLE DEVELOPMENT / EXPLORATORY STUDY ON A SAMPLE OF AUDITORS IN THE FEDERAL OFFICE OF FINANCIAL SUPERVISION (World Economics and Finance Bulletin, 2024)
The study aims to demonstrate the auditor’s commitment to International Auditing Standard No. (570) and the extent of its impact on achieving sustainable development. For the purpose of achieving the goal of the study, a questionnaire was distributed (110) of which 90 questionnaires are suitable for analysis to a sample of auditors in the Federal Office of Financial Supervision for the purpose of analyzing Their answers to determine the relationship and impact between the variables, It was discovered that there is a substantial positive association between the auditor’s commitment to International Auditing Standard 570 and sustainable development and the substantial benefits that result from auditors' dedication to International Auditing Standard 570 on sustainable development. There were several findings, the most significant of them being that the auditor’s commitment to International Auditing Standard No. (570) contributes to achieving sustainable development. Several proposals were made, the most significant of them being that the auditor must adhere to International Auditing Standard No. (570 for the objective of attaining sustainable development in the entities subject to audit.
Keywords: International; sustainable; significant; development